Unprecedented Amazonian rainforests damage during the 2023–2024 droughts - Hao Bai; Xiangzhuo Liu; Hui Yang; Jérôme Chave; Philippe Ciais; Jean-Pierre Wigneron; Sassan Saatchi; Jingfeng Xiao; Thuy Le Toan; Xiaomei Hu; Ziyan Yang; Lijun Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
Between 2023 and 2024, Amazonian rainforests experienced two consecutive, record-breaking droughts—each more intense than any previously observed—yet their impacts remain largely unquantified. Using newly developed monthly radar satellite observations (1992 to 2025) that track forest moisture and biomass dynamics, we analyzed the long-term responses of intact Amazonian rainforests to past major droughts—particularly the 2023–2024 event—and projected their post-drought recovery. We found a biome-wide sharp decline in radar signal during 2023–2024, marking the lowest level observed since 1992. Spatially, 26.8% of the forests reached their three-decade minima during this period, primarily in eastern Amazonia. This ratio is more than double that recorded during the 2005 drought, when 11.0% of the forests reached such minima. Moreover, projections based on both historical and future CMIP6 precipitation scenarios consistently indicated that, even 7 y after the 2023–2024 droughts, less than 50% of the affected areas are expected to recover to predrought conditions, and these forests are associated with lower soil cation concentrations, higher soil sand content, and lower canopy height—characteristics that lessen the risk of hydraulic failure. Given that severe droughts have occurred approximately every 7 y over the past three decades, Amazonian rainforests may face another drought before fully recovering from the 2023–2024 event. Our results therefore highlight the growing vulnerability of the Amazonian rainforests to intensifying climate extremes driven by El Niño events and ongoing anthropogenic climate change, providing evidence that these forests are approaching the limits of their preindustrial operating space.